Risk in agriculture as impediment to rural lending: the case of North-Western Kazakhstan - Martin Petrick; C. Markus Ditges (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2000)
On the basis of portfolio selection theory, this paper finds that whole-farm risk must be regarded as a major reason for the low level of credit flow to agriculture in North-western Kazakhstan. A quadratic programming model was used in order (a) to demonstrate the comparatively high overall risk exposition of a typical farm, (b) to show that an inflow of working capital could contribute to risk reduction, and (c) to illustrate short-term risk management strategies. Although there may be a role for the government in reducing risk exposition of agriculture in its current form, natural and economic constraints suggest to pave the way for structural reforms that reduce the importance of agriculture in the rural economy. – – Auf Grundlage der Portfolio selection-Theorie kommt dieser Beitrag zu dem Ergebnis, dass das einzelbetriebliche Risiko in der Landwirtschaft Nordwest-Kasachstans als ein Hauptgrund für geringen Kreditzufluss angesehen werden muss. Ein quadratisches Programmierungsmodell wurde verwendet, um (a) die vergleichbar hohe Riskoexposition eines typischen Betriebes zu verdeutlichen, (b) zu zeigen, daß ein Zufluss von Umlaufkapital zur Risikoreduktion beitragen kann und (c) kurzfristige Risikomanagement-Strategien zu illustrieren. Obwohl es bestimmte Politikoptionen zur Verminderung des Risikos in der Landwirtschaft in ihrer gegenwärtigen Form gibt, legen natürliche und ökonomische Rahmenbedingungen tiefgreifendere Strukturreformen nahe. Diese sollten dazu beitragen, mittelfristig die Bedeutung der Landwirtschaft im ländlichen Raum zu verringern.
urn:nbn:de:gbv:3:2-22891
Keywords: Q14; G11; C61; 330; Agricultural credit; Kazakhstan; Portfolio selection theory; Risk programming; Agrarkredit; Kasachstan; Portfolio selection-Theorie; Risiko-Programmierung; Agrarkredit; Kreditrisiko; Portfolio-Management; Landwirtschaft; Risikomanagement; Nichtlineare Optimierung; Kasachstan